2014
DOI: 10.4269/ajtmh.13-0711
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Dermal Leishmaniasis Caused by Leishmania siamensis in a Systemic Steroid Therapy Patient

Abstract: Leishmania siamensis infection was recently reported from Thailand. Clinical presentation of L. siamensis infections is generally related to human immunodeficiency virus infection. Herein, disseminated dermal L. siamensis infection in a systemic steroid therapy patient from Myanmar is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…He was an immunocompetent host who developed multiple erythematous and nodules on his face, trunk, and extremities after receiving steroid therapy, and afterward received a diagnosis of diffused cutaneous leishmaniasis (DCL) caused by L. martiniquensis. 20,23 His daughter, who lived in the same house, also had asymptomatic L. martiniquensis infection. 20 Until now, L. martiniquensis infection has been reported in different geographical areas, that is, Martinique Island/French West Indies, Thailand, and Myanmar (Table 1).…”
Section: Situation Of Leishmaniasis In Thailandmentioning
confidence: 99%
See 2 more Smart Citations
“…He was an immunocompetent host who developed multiple erythematous and nodules on his face, trunk, and extremities after receiving steroid therapy, and afterward received a diagnosis of diffused cutaneous leishmaniasis (DCL) caused by L. martiniquensis. 20,23 His daughter, who lived in the same house, also had asymptomatic L. martiniquensis infection. 20 Until now, L. martiniquensis infection has been reported in different geographical areas, that is, Martinique Island/French West Indies, Thailand, and Myanmar (Table 1).…”
Section: Situation Of Leishmaniasis In Thailandmentioning
confidence: 99%
“…However, the majority of lesions on skin in HIV/AIDS cases could be single, multiple nodular, or generalized papular forms. The lesion could be disseminated as multiple nonulcerative nodules, papular with ulcerative lesions or chronic generalized fibrotic lesions to other parts of the body besides a primary lesion on the face, ears (along the helix and antihelix of the pinna), the dorsum of hands, knuckles of fingers, elbows, extensor surface of the forearm, or on the trunk and lower extremities, 19,20,23,28 called DCL. For L. siamensis infection, only one DCL was reported in a person with AIDS.…”
Section: Clinical Spectrum Of L Martiniquensis and L Siamensis Infementioning
confidence: 99%
See 1 more Smart Citation
“…To date, most of the reported cases have come from southern Thailand, and the first confirmed autochthonous case was reported from this region in 1999, presenting as visceral leishmaniasis in a 3‐year‐old girl native to Surat Thani Province and who had never been abroad . Since then, several further cases have been reported from southern Thailand, including some with HIV co‐infection, and some of these with mixed symptomology of visceral and cutaneous leishmaniasis . The first case in northern Thailand, a 40‐year‐old man from Nan Province, was reported in 2005, and the second, a 52‐year‐old man from Lamphun Province, in 2012 .…”
mentioning
confidence: 99%
“…Surveys conducted in areas where L. siamensis infection has been reported in Thailand showed that Sergentomyia (Neophlebotomus) gemmea and S. (Parrotomyia) barraudi sand flies and black rats ( Rattus rattus ) were suspected to be a potential vectors and animal reservoirs for L. siamensis , respectively [12] . More recently, indigenous L. siamensis infection has been described in Myanmar in a patient who was treated with corticosteroids and in an AIDS patient [8] , [13] . L. siamensis was also detected as a causative agent of cutaneous leishmaniasis in cows and horses in Germany [14] , Switzerland [15] , and the United States [16] .…”
Section: Discussionmentioning
confidence: 99%